SOCIOLOGICAL ANALYSIS OF MAIN CHARACTER IN THE MOVIE ELEMENTAL: FORCES OF NATURE BY PETER SOHN - Dari, Putri Wulan; Anggraeni, Diana; Bowo, Tri Arie (Cahaya Ilmu Bangsa Institute, 2025)
This study examines literary works in the form of films via a sociological approach. The purpose of this study is to describe the major characters’ characterizations and define the different kinds of social interactions in Peter Sohn’s 2023 film Elemental: Forces of Nature. Using a descriptive qualitative approach, this study described sources and information as research objects, such as dialogue or transcripts and movie stills. This study made use of Tischler's social interaction theory (Nonverbal Behavioral Interaction, Exchange Interaction, Cooperative Interaction, Conflict Interaction, and Competitive Interaction) as well as Petrie and Boggs' characterization theory (Appearance, Dialogue, External Actions, Reactions from Other Characters). 32 social interaction data points were gathered for this study, which showed how social interactions influenced the main character's description based on her words, actions, and behaviors. First, two data were reflected in characterization through appearance, four data were reflected in characterization through external activities, and three data were reflected in characterization through other characters' reactions in social interactions that took the form of nonverbal behavioral exchange. In addition, social contacts in the form of exchange encounters revealed that two data were represented in characterization through other characters' reactions, four data were reflected in characterization of external activities, and five data were reflected in characterization through dialogue. Subsequently, five data were represented in characterization through external actions, and one data was reflected in characterization through discussion in the form of cooperative social engagement. Lastly, social interactions in the form of conflict interaction revealed two data represented in appearance characterization, three data reflected in dialogue characterization, and one data reflected in other characters' reactions. This investigation did not find any competitive interaction. According to the study's findings, the primary character's characterization varies as a result of the social interactions in its environment.